Analysis of differences in variables related to health and safety according to the employment type of Korean workers - Jung, Hyun-Ok; Han, Seung-Woo (International Journal of Occupational Safety and Health, 2022)
Introduction: The purpose of this study was to understand the differences in variables related to health and safety according to the employment type of Korean workers, specifically to identify the differences by employment type on in health status, the likelihood of wearing protective gear when working, access to manuals on emotional expression, and access to information on risk factors related to health and safety. Methods: The secondary data of four items on employment type, health type of workers and safety among the 5th Korean Working Condition Survey conducted in 2017 in Korea was used in this study. The data of workers were processed by using SPSS/WIN 23.0 Program and R 3.1.2, and demographic characteristics were quantified as frequency and percentage. Results: A total of 30,300 employed people were surveyed. The result shows that part-time workers have poorer health than full-time workers (c2 = 540.7155, p < 0.05), insufficiently wore protective gear (c2 = 24.8702, p < 0.05), had insufficient access to manuals on emotional expression (c2 = 27.7612, p < 0.05) and lacked information about risk factors (c2 = 185.0082, p < 0.05). Conclusion: Health and safety manager will need to have education and consultation, development of manual and perform an early intervention to improve safety environment as primary health care providers by understanding factors related to health and safety of part-time workers.